2001
DOI: 10.1002/ccd.1178
|View full text |Cite
|
Sign up to set email alerts
|

Use of fenoldopam to prevent radiocontrast nephropathy in high‐risk patients

Abstract: We evaluated the ability of fenoldopam, a newly available renal vasodilator, to prevent radiocontrast nephropathy in high-risk patients undergoing interventional diagnostic and therapeutic angiographic procedures. We reviewed the results from 46 consecutive procedures in patients with serum creatinine > or = 1.5 mg/dL if diabetic and > or = 1.7 mg/dL if nondiabetic. We compared our results to a previously published cohort of similarly at-risk patients. The incidence of radiocontrast nephropathy, defined as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 24 publications
0
67
1
Order By: Relevance
“…25 The benefit of fenoldopam for the prevention of contrast-medium nephropathy has been demonstrated in a dog model and in nonrandomized clinical studies. 25,[59][60][61] In a small double-blind, randomized controlled pilot trial, fenoldopam plus normal saline was found to attenuate reductions in renal blood flow induced by contrast media; it was also associated with a lower incidence of contrast-medium nephropathy than was normal saline alone, although the difference between the 2 groups was not significant. 62 The benefit of fenoldopam was not validated in a large multicentre randomized placebo-controlled double-blind trial.…”
Section: Vasodilatorsmentioning
confidence: 99%
“…25 The benefit of fenoldopam for the prevention of contrast-medium nephropathy has been demonstrated in a dog model and in nonrandomized clinical studies. 25,[59][60][61] In a small double-blind, randomized controlled pilot trial, fenoldopam plus normal saline was found to attenuate reductions in renal blood flow induced by contrast media; it was also associated with a lower incidence of contrast-medium nephropathy than was normal saline alone, although the difference between the 2 groups was not significant. 62 The benefit of fenoldopam was not validated in a large multicentre randomized placebo-controlled double-blind trial.…”
Section: Vasodilatorsmentioning
confidence: 99%
“…Observational studies reported rather low rates of CIN in high-risk patients treated with fenoldopam [17,75,76]. In a double-blind, randomized, placebo-controlled pilot trial [77], the combination of fenoldopam and hydration, compared with hydration alone, resulted in an increase in renal plasma flow, a decrease in peak serum creatinine level 72 hr after exposure to contrast media, and a trend toward decreased incidence of CIN (21% and 41%, respectively; P ¼ 0.14).…”
Section: Fenoldopammentioning
confidence: 99%
“…There are several data assuming the direct tubular toxicity of the contrast media as a pathophysiological mechanism for the development of CIN. 6,15 Contrast media can also damage renal tubular cells via oxygen radicals. 16 Several clinical and experimental studies documented a significant correlation between proteinuria and progression of renal failure.…”
Section: 12mentioning
confidence: 99%